2020
DOI: 10.3390/nu12051463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Nutrient-Based Indices against Food- and Diet-Based Indices to Assess the Health Potential of Foods: How Does the Australian Health Star Rating System Perform after Five Years?

Abstract: Nutrient-based indices are commonly used to assess the health potential of individual foods for nutrition policy actions. This study aimed to evaluate the nutrient profile-informed Australian Health Star Rating (HSR), against NOVA and an index informed by the Australian Dietary Guidelines (ADGs), to determine the extent of alignment. All products displaying an HSR label in the Australian marketplace between June 2014 and June 2019 were extracted from the Mintel Global New Product Database, and classified into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 55 publications
5
31
1
Order By: Relevance
“…Differences in the database dates used, target sample and/or the product sample size could explain these differing proportions of foods displaying an HSR. Bakery and Snacks categories were the most prevalent products displaying an HSR, as also found by Lawrence et al and Dickie et al [37,38]. The food categories in this study that did not have any products displaying an HSR were mostly discretionary foods, for example, Chocolate Confectionary and Sugar and Gum Confectionery.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Differences in the database dates used, target sample and/or the product sample size could explain these differing proportions of foods displaying an HSR. Bakery and Snacks categories were the most prevalent products displaying an HSR, as also found by Lawrence et al and Dickie et al [37,38]. The food categories in this study that did not have any products displaying an HSR were mostly discretionary foods, for example, Chocolate Confectionary and Sugar and Gum Confectionery.…”
Section: Discussionsupporting
confidence: 83%
“…An HSR was displayed on 18.2% of products examined in this study. This result is higher than that obtained in a study by Lawrence et al, who found that 10.5% of new products (using Mintel's GNPD) released between 27th June 2014 and 27th June 2017 displayed an HSR, and a study by Dickie et al using the same database but for the time period 6 June 2014-30 June 2019, who found an HSR on 17.6% of products [37,38]. Differences in the database dates used, target sample and/or the product sample size could explain these differing proportions of foods displaying an HSR.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Nutrient‐centric approaches can also stimulate the production and promotion of UPFs. For example, between 2014 and 2019, the Australian nutrient‐based Health Star Rating (HSR) system approved between 73% and 77% of UPFs using the system to display a ‘pass mark’ of 2.5 stars or more (out of a possible 5) on labels 196,197 . Food‐based dietary guidelines (FBDGs) adopted in most countries are a foundation for nutrition policy and guidance 193,198 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, between 2014 and 2019, the Australian nutrient-based Health Star Rating (HSR) system approved between 73% and 77% of UPFs using the system to display a 'pass mark' of 2.5 stars or more (out of a possible 5) on labels. 196,197 Foodbased dietary guidelines (FBDGs) adopted in most countries are a foundation for nutrition policy and guidance. 193,198 Yet, a large majority of FBDGs adopt a nutrient-centric approach, recommending to limit foods high in certain risk nutrients or 'energy-dense and nutrient-poor' foods.…”
Section: Policy Regulatory and Political Economy Driversmentioning
confidence: 99%